Coupled Coating Formation Simulation in Thermal Spray Processes using CFD and FEM - Prehm, J.; Xin, L.; Möhwald, K.; W. Bach, Fr. (CFD Letters, 2021)
This paper deals with the simulation of coating formation in Thermal Spray processes. That means that impingement and flattening of molten metal- or ceramic particles with a diameter of about 50 microns on a rough surface have to be regarded. In this work, this is accomplished use of the Volume of Fluid method. The disadvantage here is that only the pure flattening process can be considered. In order to implicate the shrinking of the particles due to cooling down after solidification, which is responsible for the occurrence of pores and thermal stresses, a Finite Element calculation is done subsequent to the CFD-calculation. After the FEM calculation has finished, the newly generated, shrinked particle shape has to be re-imported into the CFD grid.